Validation of a full-body computer simulation of the golf drive for clubs of differing length - Fozzy Moritz, E.; Haake, S.; Kenny, I. C.; Wallace, E. S.; Brown, D.; Otto, S. R. (The Engineering of Sport 6, Volume 2 Developments for Disciplines, 2006)
The aim of the present study was to validate a full-body computer simulation of a golfer`s swing for driving clubs. An elite male golfer performed 24 shots in a laboratory, comprised of 8 trials using each of three drivers of different shaft length (46, 48, 50). A 5-camera MACTM system operating at 240 Hz collected kinematic data which was subsequently used to drive the model utilising ADAMS/LifeMOD software. Additional skin markers were used for model validation. A large-scale musculoskeletal human model was constructed, with a parametric model of a driver. Inverse and forward dynamics calculations were performed with the imported experimental motion data in order to generate model movement. A commercially available launch monitor recorded experimental eclubhead and launch conditions. There was a very high level of agreement (r=0.995) between experimental kinematic data and the predicted trjectory splines of the model. There was also a high level of correlation (r=0.989) between the model predicted mean values for clubhead speed and the experimental values for each of the club lengths, both demonstrating increased clubhead velocity as club length increased. Muscle contraction force output by the model showed a significant difference between driver simulations, demonstrating its capability to illustrate the link between gross muscle force production and club length, as evidenced by the increased force output for the longest shafted club.